It’s Not Just a Matter of Time: Exploring Resistance to Indigenous Education - Leddy, Shannon; O'Neill, Susan (Alberta Journal of Educational Research, 2021)
This article explores resistance that occurred during the implementation of an Indigenous education curriculum within a teacher education program. The goal was to assist student teachers (STs) in developing a level of decolonial literacy that would help them unearth the colonial roots of their prior Indigenous education. Multiple data sources (STs written reflections, email communications, and researcher observations), were analyzed using narrative analysis to illuminate instances of resistance. Although the project showed great promise for transformative learning, the manifestation of resistance indicates the dire need for such work to continue. In our conclusion we offer some key considerations for teacher education regarding approaches to Indigenous education. Key Words: Indigenous Education, anti-racist education, resistance, teacher education, arts education Cet article explore la résistance qui était produit pendant l’implémentation d’un programme autochtone dans un programme de formations des enseignants. Le but de ce programme était d’encourager le développement d’alphabétisation décoloniale pour révéler les racines coloniales de leur éducation précédente. Plusieurs sources de données ont utilisé (des réflexions écrites, les communications courriel, et les observations des chercheurs) et ont analysé par méthode de l’analyse narrative pour illuminer des instances de résistance. Bien que le projet démontre beaucoup de potentiel, les manifestations de résistance indiquent le besoin vital pour ce travail a continué. En conclusion, nous offrons des considérations clé pour des programmes autochtones dans les programmes de formation d’enseignants. Mots clés: Éducation autochtone, éducation antiraciste, résistance, formation des enseignants, éducation artistique